Patients with Rheumatoid Arthritis and Chronic Pain Display Enhanced Alpha Power Density at Rest - Meneses, Francisco M.; Queirós, Fernanda C.; Montoya, Pedro; Miranda, José G. V.; Dubois-Mendes, Selena M.; Sá, Katia N.; Luz-Santos, Cleber; Baptista, Abrahão F. (Frontiers in Human Neuroscience, 2016)
Patients with chronic pain due to neuropathy or musculoskeletal injury frequently exhibit reduced alpha and increased theta power densities. However, little is known about electrical brain activity and chronic pain in patients with rheumatoid arthritis (RA). For this purpose, we evaluated power densities of spontaneous electroencephalogram (EEG) band frequencies (delta, theta, alpha, and beta) in females with persistent pain due to RA. This was a cross-sectional study of 21 participants with RA and 21 healthy controls (mean age = 47.20; SD = 10.40). EEG was recorded at rest over five minutes with participant's eyes closed. Twenty electrodes were placed over five brain regions (frontal, central, parietal, temporal, and occipital). Significant differences were observed in depression and anxiety with higher scores in RA participants than healthy controls (p = .002). Participants with RA exhibited increased average absolute alpha power density in all brain regions when compared to controls (F (1.39) = 6.39, p = .016), as well as increased average relative alpha power density (F (1.39) = 5.82, p = .021) in all regions, except the frontal region, controlling for depression/anxiety. Absolute theta power density also increased in the frontal, central, and parietal regions for participants with RA when compared to controls (F(1,39) = 4.51, p = .040), controlling for depression/anxiety. Differences were not exhibited on beta and delta absolute and relative power densities. The diffuse increased alpha may suggest a possible neurogenic mechanism for chronic pain in individuals with RA.